Decreasing viscosity and increasing accessible load by replacing classical diluents with a hydrotrope in liquid–liquid extraction - El Maangar, Asmae; Zemb, Thomas; Fleury, Clément; Duhamet, Jean; Dufrêche, Jean-François; Pellet-Rostaing, Stéphane (Frontiers in Chemical Engineering, 2025)
We show here on a generic example that the strategy of replacing a classically used aliphatic diluent with a hydrotrope in liquid-liquid extraction induces higher performances. Liquid-liquid extraction is widely used in hydrometallurgical processes for the recycling of strategic metals but it is limited because of the formation of a 3 rd phase. Hydrotopes have never been studied as diluent in the context of metal recycling. We show in that work that using hydrotropes as diluent decrease by more than a factor of ten the viscosity of the solutions, even under high loaded by extracted cations and and at the same time, of an increase of the efficiency of extraction for typical ionic extractants such as anionic phosphates or non-ionic amides. The latter also quenches all types of third-phase transitions that occur when classical diluents are used. The gain in distribution coefficient by a factor of ten comes from the entropy of the solvent phase involved and is not linked to apparent complexation constants. In the case of anionic extractants, the Gibbs energy of transfer depends linearly on the ionic radii of the rare earth considered, this is not true with non ionic extractants. Last but not least, the maximum load possible is increased by a factor of 2-3 versus alkanes, allowing more compact design and intensification of extraction processes. Based on SAXS and surface tension mesaurements, the origin of this gain in Gibbs energy of transfer and tunable selectivity in the family of rare earth elements is further identified by three mechanisms : reduction of the term linked to complexation, more than compensated by a synergistic effect of the hydrotrope and the comlexant as well as an intra-aggregate the intra-aggregate entropy of mixing. The oreal result is a systematic increase of distribution coeeficient of the order of 50 to 150 of the distribution coefficients, induced systematically by the replacement of alcanes by hydrotropes as diluents.